(untitled) (Journal of Pathology of Nepal, 2021)
Background: The prostate is a walnut-sized organ that surrounds the urethra. More than 99% of prostate cancers are prostatic adenocarcinoma. It is the second most commonly occurring cancer in men and the fourth most commonly occurring cancer in India and all over the world. Numerous lesion of the prostate are very similar to prostate cancer, hence awareness is very important. This study aimed to determine the histopathological features of prostate adenocarcinoma and its common mimickers. Materials and Methods: A retrospective study of histopathological features of radical prostatectomy and transurethral resection of the prostate specimens, sent to the department of pathology for a period of one year. A brief clinical history and serum prostate-specific antigen levels were noted. Results: The surgical specimens of 303 cases of prostatic diseases were studied. Benign prostatic hyperplasia was the most frequent diagnosis in 192 patients followed by Prostate adenocarcinoma seen in 80 patients. Prostatic intraepithelial neoplasia formed the predominant mimicker (5.9%), followed by basal cell hyperplasia (3.0%). Serum prostate-specific antigen was seen in the range of 1.73 - 100 ng/ml in the cases of adenocarcinoma. In the mimics, prostate-specific antigen was in the range of 1.2- 18ng/ml. Conclusions: Biopsy remains a gold standard for the diagnosis of adenocarcinoma and its mimickers. The lesions in this study were diagnosed on hematoxylin and eosin staining.